Characterization of Aeromonas hydrophila Strains Isolated from Carp Culture Pond Water: Virulence, Antibiotic Resistance, and Pathogenicity Evaluation - Behera, Satyajit; Pradhan, Subham Kumar; Devi, Rajashree; Choudhury, Tanmoy Gon; Kamilya, Dibyendu; Dekari, Debojit (Fishery Technology, 2025)
Aeromonas hydrophila, a notorious pathogen inaquaculture, poses significant threats to fish health and industry sustainability, necessitating detailed investigations into its identity, virulence mechanisms, and antibiotic resistance. This study evaluated the identity, virulence properties, and antibiotic susceptibility of four A. hydrophila strains (COFCAU_AH1, COFCAU_AH2, COFCAU_AH3, COFCAU_AH4) isolated from carp culture pond water in Tripura, India. The strains were confirmed as A. hydrophila through a combination of morphological, physiological, biochemical analyses, and 16S rRNA gene sequencing. All strains were susceptible to several antibiotics but some showed resistance to kanamycin, tobramycin, and polymyxin B. Virulence genes such as hlyA, alt, ast, ela, and ascC were found in COFCAU_AH3, and COFCAU_AH4,while the lipase gene (lip) was present in all fourstrains. The in vivo pathogenicity test determined the LD50 for COFCAU_AH1, COFCAU_AH3 andCOFCAU_AH4 as 109.5, 104.4, and 104.5 cells/fish,respectively, with no mortality in fish exposed toCOFCAU_AH2. Infected fish displayed clinicalsigns like exophthalmia, scale erosion, fin and tailrot, hemorrhages, and abdominal dropsy. Thesefindings highlight the risk of virulent A. hydrophilastrains in aquaculture, emphasizing the need foreffective monitoring and management.